Practicing Lament to Teach for Justice: Reflections from a Survey Course. Issue 3 (27th May 2018) - Huff, James G.
ABSTRACT: What pedagogical routines and rhythms can teachers in Christian institutions of higher education adopt to teach for justice? The article explores this question by detailing efforts to incorporate the practice of lament into the learning routines of a survey course on global poverty. Drawing on recent scholarship on practice-oriented pedagogies and lament theology, the discussion articulates a lament pedagogy that aims to deepen students' empathetic engagement with the voices of suffering they encounter in the course and to engender a performative response to injustices they confront beyond the classroom. In particular, the article details how the use of literary accounts written by non-Western authors who explore themes of disruptive social change, poverty, and injustice in their works intersects with an overarching practice of lament to foster enduring processes of dispositional formation in students. A closing discussion considers how the pedagogical routines developed in a global poverty course might be adapted to and implemented in courses across the liberal arts curriculum. The article makes the case that educators in Christian colleges and universities are critical in the ongoing public recovery of a practice of prayer and worship that is fundamental to one's engagement with suffering in the world.